Financial frictions and regime switching: The role of collateral asset in emerging stock market - Haithem Awijen; Sami Hammami (Kiel Institute for the World Economy (IfW), 2017)
This paper examines empirically the nonlinear business cycle dynamics due to the presence of financial frictions. Using a threshold vector auto regression, the authors estimate the behavior of interest rate shocks in which a regime change occurs if the two respective threshold variables namely asset price and exchange rate cross their critical threshold value. The authors find evidence that non linearity is strongly directed by regime-dependency; in fact the results suggest that output growth response is bigger when the economy is initially an appreciation regime.In addition, the empirical findings prove the presence of asymmetric responses to interest rate shocks however this reaction is recognized via asset price "debt-deflation mechanism" rather than shocks stemming from "exchange rate depreciation spirals". The results also show that a response to large shocks to interest rate shows disproportionate effects compared with responses to small shocks.
Keywords: E51; E32; C20; C63; 330; Collateral Constraints; Business Cycle Asymmetry; financial frictions; Threshold VAR